2012
DOI: 10.1007/s11914-012-0117-0
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Injury-Induced Osteoporosis: Pathogenesis and Emerging Therapies

Abstract: Spinal cord injury causes rapid, severe osteoporosis with increased fracture risk. Mechanical unloading after paralysis results in increased osteocyte expression of sclerostin, suppressed bone formation, and indirect stimulation of bone resorption. At this time there are no clinical guidelines to prevent bone loss after SCI and fractures are common. More research is required to define the pathophysiology and epidemiology of SCI-induced osteoporosis. This review summarizes emerging therapeutics including anti-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(112 citation statements)
references
References 82 publications
0
107
0
5
Order By: Relevance
“…досягає 20-50 % мінеральної щільності кісткової тка-нини (МЩКТ) паралізованих кінцівок [3]. Тривалість підвищення темпів резорбції кісткової тканини після ТХСМ залишається дискутабельним питанням.…”
Section: вступunclassified
See 1 more Smart Citation
“…досягає 20-50 % мінеральної щільності кісткової тка-нини (МЩКТ) паралізованих кінцівок [3]. Тривалість підвищення темпів резорбції кісткової тканини після ТХСМ залишається дискутабельним питанням.…”
Section: вступunclassified
“…Паралельно також відбувалося стоншення кортикального шару довгих трубчастих кісток ниж-ніх кінцівок, але втрата кортикального шару відбува-лася значно повільніше, ніж трабекулярної кісткової тканини. Саме повільне стоншення кортикального шару може пояснити, що середній період до настан-ня першого перелому в пацієнтів із ТХСМ становить 9 років після травми [3]. Отже, корекція структур-но-функціонального стану кісткової тканини як за-побігання перелому має досить велике терапевтичне вікно -9 років.…”
Section: обговоренняunclassified
“…The preventive effects of non-pharmacological interventions utilizing standing, walking, functional electrical stimulus or ultrasound on bone loss remain controversial. 1,9,[14][15][16] The effects of such interventions differed depending on research conditions, including subjects, methods, devices and interventions; for example, passive physical activity by standing was ineffective, whereas muscle contraction by functional electrical stimulus was effective. 1,9,[14][15][16] Whole-body vibration (WBV) has been reported as a potent intervention for maintenance and/or enhancement of bone tissue in people with low levels of BMD, in elderly post-menopausal women and in adolescents.…”
Section: Osteoporosis Is a Well-known Complication Of Spinal Cord Injmentioning
confidence: 99%
“…1,9,[14][15][16] The effects of such interventions differed depending on research conditions, including subjects, methods, devices and interventions; for example, passive physical activity by standing was ineffective, whereas muscle contraction by functional electrical stimulus was effective. 1,9,[14][15][16] Whole-body vibration (WBV) has been reported as a potent intervention for maintenance and/or enhancement of bone tissue in people with low levels of BMD, in elderly post-menopausal women and in adolescents. [17][18][19] In SCI patients, a combination of standing and WBV increased BMD in the trunk and spine, 20 whereas low-magnitude WBV improved the deterioration of neither the BMD in the distal femur nor the microstructure in the proximal tibia.…”
Section: Osteoporosis Is a Well-known Complication Of Spinal Cord Injmentioning
confidence: 99%
“…2 Morganti et al 3 reported that~90% of complete SCI patients are dependent on a wheelchair. The long-term use of a wheelchair causes medical problems 4 and psychosocial problems as the result of a relatively low eye level. 5,6 Thus, gait reconstruction in such patients has been a key issue in rehabilitation medicine.…”
Section: Complete Motor Spinal Cord Injury (Sci) Patients (American Smentioning
confidence: 99%